Electric Stimulation of Charge-Discharge Processes of Electrochemical Capacitors - Budzulyak, I.M.; Rachiy, B.I.; Vashchynsky, V.M.; Ivanichok, N.Ya.; Lutsas А.V.; Nykoliuk, M.O. (Physics and Chemistry of Solid State, 2015)
The research is devoted to study the impact of charge-discharge processes in electrochemical capacitors. Nanoporous carbon material was used like electrode material , which was gotten through carbonization of raw plant material. The supercapacitor model and main mode parameters of operation were chosen for this experiment. Experimental data were gotten, where we make the conclusion, that the long-term processing of electric stimulation enhances capacity properties of electrochemical capacitors.